Method for producing alkaline earth aluminosilicate glass

By introducing alkali metal oxides using alkali feldspar raw materials, the method addresses the issues of undissolved silica and reboiling in alkaline earth aluminosilicate glass production, enhancing melt homogeneity and reducing bubble defects.

JP7610176B2Active Publication Date: 2025-01-08NIPPON ELECTRIC GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020117461
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-08
Publication Date
2025-01-08
Estimated Expiration
2040-07-08

AI Technical Summary

Technical Problem

Existing methods for producing alkaline earth aluminosilicate glass face challenges in preventing undissolved silica and excessive reboiling during the melting process, leading to bubble defects and inefficient production.

Method used

Using an alkali feldspar raw material to introduce alkali metal oxides, which delays the formation of an alkali-containing melt, reduces basicity differences, and enhances melt homogeneity, thereby suppressing reboiling and undissolved silica separation.

Benefits of technology

The method effectively reduces reboiling and undissolved silica separation, resulting in a more homogeneous melt and improved glass quality suitable for display substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610176000001
    Figure 0007610176000001
Patent Text Reader

Abstract

To provide a manufacturing method of alkaline-earth aluminosilicate glass unlikely to lead to non-melting silica or fusion separation at melting a glass batch and difficult to cause reboil.SOLUTION: A manufacturing method of alkaline-earth aluminosilicate glass in the present invention is configured to formulate raw materials to prepare a glass batch, and thereafter to fuse, clarify and mold the obtained glass batch to manufacture alkaline-earth aluminosilicate glass. A content of an alkali metal oxide in the alkaline-earth aluminosilicate glass is 0.01 to 1 mass%. An alkali feldspar material is used as an introduction material of the alkali metal oxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing alkaline earth aluminosilicate glass, and more particularly to a method for producing alkaline earth aluminosilicate glass used for substrates of liquid crystal displays and organic EL displays. [Background technology]

[0002] Non-alkali glass plates, that is, non-alkali alkaline earth aluminosilicate glass plates, are used as substrates for liquid crystal displays and the like.

[0003] In recent years, attempts have been made to increase the productivity of glass plate substrates for liquid crystal displays and organic electroluminescence displays by allowing the use of alkali metal oxides (Li2O, Na2O, K2O) to the extent that they do not adversely affect the devices. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-265001 A [Patent Document 2] JP 2012-148959 A Summary of the Invention [Problem to be solved by the invention]

[0005] For example, Patent Document 1 discloses that by adding 0.03 mass % or more and less than 0.1 mass % of an alkali metal oxide to the glass composition to increase the basicity of the glass, the solubility of SO3 in the molten liquid during melting is improved, and the bubble-suppressing effect of SO3 as a fining agent is enhanced while suppressing the generation of reboil bubbles after the fining reaction.

[0006] Many alkali salts, such as alkali carbonates, melt or react in the early stages of the vitrification reaction of the glass batch, so when melting a glass batch containing alkali salts, the melt formed in the early stages of melting has a high alkali content. Therefore, the melt formed in the early stages of the vitrification reaction of a glass batch containing alkali salts becomes too basic and incorporates excessive SO3. After that, poorly soluble components such as SiO2 and Al2O3, which have low basicity, melt or react with the initial melt. At that time, the initial melt rich in alkali metals has a high basicity, and the difference in basicity between it and the melt containing a lot of SiO2 and Al2O3 formed later is large, so the sulfur components reboil and cause bubble defects.

[0007] Patent Document 2 discloses that the fining effect is enhanced by using alumina containing Na2O, which is an impurity, in the range of 0.1 to 0.6 mass % as a raw material for introducing Al2O3.

[0008] However, since Na2O contained in this alumina remains near the alumina even after the glass batch is mixed, it is difficult to contribute to the reaction with the silica raw material. Therefore, even if the alumina described in Patent Document 2 is introduced, the effect of suppressing melt separation due to undissolved silica is insufficient, and further, the suppression of reboil is also insufficient.

[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to devise a method for producing alkaline earth aluminosilicate glass in which silica is less likely to remain undissolved or to separate during melting when a glass batch is melted, and in which reboiling is less likely to occur. [Means for solving the problem]

[0010] As a result of intensive research, the present inventors have found that the above technical problems can be solved by using an alkali feldspar raw material as a raw material for introducing an alkali metal oxide of an alkaline earth aluminosilicate glass, and propose this as the present invention. That is, the method for producing an alkaline earth aluminosilicate glass of the present invention is a method for producing an alkaline earth aluminosilicate glass by mixing raw materials to prepare a glass batch, and then melting, fining, and forming the obtained glass batch to produce an alkaline earth aluminosilicate glass, characterized in that the content of the alkali metal oxide in the alkaline earth aluminosilicate glass is 0.01 to 1 mass %, and an alkali feldspar raw material is used as a raw material for introducing an alkali metal oxide. Here, the "alkali feldspar raw material" refers to feldspar or feldspar containing an alkali component such as orthoclase (KAlSiO8) or albite (NaAlSiO8), a solid solution of feldspar or feldspar containing at least a part of an alkali component, or a mixture thereof. Note that the "alkali feldspar raw material" may contain impurities such as quartz and anorthite in addition to containing an alkali component.

[0011] In alkaline earth aluminosilicate glass used for display substrates, alkali salts such as alkali carbonates, alkali nitrates, alkali sulfates, and alkali halides have been used as the raw material for introducing alkali metal oxides. Since the decomposition temperature and reaction temperature of most alkali salts are lower than the melting point of the alkali feldspar raw material, they form a melt earlier than other raw materials during the vitrification reaction of the glass batch and react with the components of the glass batch. The melt containing the alkali component has a high basicity. When the alkali salt is introduced, the melt containing the alkali component is formed at the beginning of the batch reaction. Thereafter, the basicity of the melt is homogenized by the melting of the low basicity components and the convection and stirring of the melt. When the alkali salt is introduced, the sulfur solubility of the melt formed at the beginning of the melting is excessively high, and as the vitrification reaction proceeds, the sulfur solubility decreases, so that the melt is more likely to reboil. As described above, the alkali components contained as impurities in the alumina raw material are poorly soluble in alumina, and therefore the alkali components in the alumina rarely come into contact with other raw materials, particularly the silica raw material, and are unlikely to contribute to suppressing melting and separation due to undissolved silica.

[0012] However, in the present invention, by using an alkali feldspar raw material as a raw material for introducing an alkali metal oxide, it is possible to suppress melt separation during melting of the glass batch, reduce local differences in the amount of dissolved sulfur in the molten liquid, and suppress reboiling.

[0013] The reason for using an alkali feldspar raw material as the raw material for introducing an alkali metal oxide will be described in detail below. The melting temperature of the alkali feldspar raw material is lower than that of SiO2 and Al2O3, which are poorly soluble raw materials, and higher than the melting temperature and reaction temperature of the alkali salt. Therefore, by using an alkali feldspar raw material, the formation of an alkali-containing melt can be delayed compared to the case where an alkali salt is used. If the alkali content of the melt formed at the beginning is reduced, the basicity of the melt formed at the beginning is reduced, so that the increase in the amount of sulfur dissolved in the melt formed at the beginning can be suppressed. In addition, since the melt of the alkali feldspar raw material becomes a mixed melt of an alkali metal oxide, SiO2, and Al2O3, it has a composition closer to that of an alkaline earth aluminosilicate glass than the melt of an alkali salt or an alkali metal oxide formed when an alkali salt is used, and the homogeneity of the melt can be improved. Furthermore, since the amount of silica raw material, which is a poorly soluble raw material, used can be reduced, melt separation due to undissolved silica can be suppressed. From the above, when the alkali metal oxide is introduced from the alkali feldspar raw material, it is possible to form a homogeneous melt while suppressing an increase in the basicity of the melt formed in the initial stage, and therefore it is possible to significantly suppress reboiling.

[0014] As described above, the alkali feldspar raw material contains an alkali component that deteriorates the display characteristics. For example, when albite is used as the alkali feldspar raw material, about 12 mass% of Na2O in the albite is introduced into the glass composition. When orthoclase is used as the alkali feldspar raw material, about 17 mass% of K2O in the orthoclase is introduced into the glass composition. However, when a silica raw material or an alumina raw material is used in addition to the alkali feldspar raw material, the content of alkali metal oxide in the alkaline earth aluminosilicate glass can be restricted to 0.01 to 1 mass%. According to the present inventor's research, if the content of alkali metal oxide in the alkaline earth aluminosilicate glass is 1 mass% or less, it is acceptable because it does not deteriorate the display characteristics much.

[0015] In the method for producing alkaline earth aluminosilicate glass of the present invention, the alkaline earth aluminosilicate glass preferably has a sulfur content of 0.1 to 100 ppm by mass in terms of SO3.

[0016] In the method for producing alkaline earth aluminosilicate glass of the present invention, the alkaline earth aluminosilicate glass preferably has a B2O3 content of 15 mass % or less.

[0017] In the method for producing alkaline earth aluminosilicate glass of the present invention, the total amount of alkaline earth metal oxides (MgO+CaO+SrO+BaO) in the alkaline earth aluminosilicate glass is preferably 1 to 40 mass %.

[0018] In the method for producing alkaline earth aluminosilicate glass of the present invention, the alkaline earth aluminosilicate glass is preferably used as a substrate for a display. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The method for producing alkaline earth aluminosilicate glass of the present invention is a method for producing alkaline earth aluminosilicate glass by blending raw materials to prepare a glass batch, and then melting, fining, and forming the obtained glass batch to produce alkaline earth aluminosilicate glass, characterized in that the content of alkali metal oxide in the alkaline earth aluminosilicate glass is 0.01 to 1 mass %, and an alkali feldspar raw material is used as a raw material for introducing the alkali metal oxide. The method for producing alkaline earth aluminosilicate glass of the present invention will be described in detail below.

[0020] First, raw materials that are the sources of each component are prepared and mixed to produce a glass batch so as to obtain the desired glass composition and glass characteristics. If necessary, glass cullet may be used as the raw material. Glass cullet is glass waste discharged during the glass manufacturing process.

[0021] In the present invention, raw materials containing an alkali feldspar raw material are mixed, and an alkali feldspar raw material is used as all or part of the alkali-introducing raw material, and preferably the majority of the alkali content in the glass composition is introduced as an alkali feldspar raw material, and more preferably 80 mass % or more of the alkali content in the glass composition is introduced as an alkali feldspar raw material. A melt of an alkali aluminosilicate is formed by dissolving the alkali feldspar raw material. The melt of an alkali aluminosilicate contains sparingly soluble SiO2 and Al2O3 in a molten state, so that the homogeneity of the melt can be improved. On the other hand, when an alkali salt is used as the alkali-introducing raw material, an initial melt of high basicity containing an alkali is formed. After that, the difference in basicity with a low basicity component such as silica (SiO2) dissolved in the melt becomes large, and reboiling is easily caused.

[0022] When comparing the case where an alkali feldspar raw material is used as an alkali introduction raw material with the case where an alkali salt is used, the initial melt contains fewer alkali components and has a lower basicity when the alkali feldspar raw material is used. The alkali feldspar raw material that melts thereafter has a higher basicity than silica. Therefore, the difference in basicity between the initial melt and the alkali feldspar raw material components becomes smaller, making it difficult for reboiling to occur.

[0023] Among the raw materials, the raw material for introducing silica is poorly soluble, while the raw materials for introducing alkaline earth oxide, boron oxide, and alkali metal oxide are easily soluble. Since alkaline earth oxide has a low melting point and a high density, it melts and liquids in the early stage of the melting process and tends to sink. On the other hand, since silica has a high melting point and a low density, it tends to float relatively easily. Therefore, if an alkali feldspar raw material is used as the raw material for introducing alkali metal oxide, the amount of undissolved silica can be reduced, and the degree of melting and separation can be reduced.

[0024] In the method for producing alkaline earth aluminosilicate glass of the present invention, it is preferable to prepare a glass batch by blending and mixing raw materials so that the glass composition contains, in mass % calculated as the oxides below, 50-70% SiO2, 10-25% Al2O3, 0-15% B2O3, 0.01-1% Li2O+Na2O+K2O, 0-8% MgO, 3-10% CaO, and 1-40% MgO+CaO+SrO+BaO. The reasons for limiting the glass composition as above are as follows. In the explanation of the content range of each component, % indicates mass %.

[0025] SiO2 is a component that forms the skeleton of glass. The content of SiO2 is preferably 50 to 70%, 54 to 68%, 56 to 66%, and particularly 58 to 64%. If the content of SiO2 is too low, the density becomes too high and the acid resistance is likely to decrease. On the other hand, if the content of SiO2 is too high, the high-temperature viscosity becomes high, the melting property is likely to decrease, and devitrified crystals such as cristobalite are likely to precipitate, and the liquidus temperature is likely to increase.

[0026] Al2O3 is a component that forms the skeleton of glass, increases the strain point and Young's modulus, and inhibits phase separation. The content of Al2O3 is preferably 10 to 25%, particularly 15 to 22%. If the content of Al2O3 is too low, the strain point and Young's modulus tend to decrease, and the glass tends to undergo phase separation. On the other hand, if the content of Al2O3 is too high, devitrified crystals such as mullite and anorthite tend to precipitate, and the liquidus temperature tends to increase.

[0027] B2O3 is a component that enhances meltability and devitrification resistance. The content of B2O3 is preferably 0 to 15%, 0.1 to 6%, 0.3 to 3%, and particularly 0.5 to 2.3%. If the content of B2O3 is too low, the meltability and devitrification resistance are likely to decrease, and the resistance to hydrofluoric acid-based chemicals is likely to decrease. On the other hand, if the content of B2O3 is too high, the Young's modulus and strain point are likely to decrease.

[0028] Alkali metal oxides (Li2O, Na2O, K2O) are essential components for lowering the melting temperature and molding temperature, and for reducing melt separation due to undissolved silica. However, if the content of alkali metal oxides is too high, it will have a negative effect on the performance of the display. Therefore, the content of Li2O+Na2O+K2O (total amount of Li2O, Na2O and K2O) is preferably 0.01 to 1%, 0.02 to 0.75%, 0.03 to 0.5%, and particularly 0.04 to 0.5%. In the present invention, the alkali metal oxide is mainly introduced from the alkali feldspar raw material, but the alkali metal oxide may be introduced from a raw material other than the alkali feldspar raw material. For example, the alkali metal oxide may be introduced from a raw material such as a lithium salt, a sodium salt, or a potassium salt, or the alkali metal oxide may be introduced as an impurity of another raw material.

[0029] MgO is a component that reduces high-temperature viscosity and increases melting property, and among alkaline earth metal oxides, it is a component that significantly increases Young's modulus. The content of MgO is preferably 0 to 8%, 1 to 7%, 2 to 6%, and particularly 2.5 to 6%. If the content of MgO is too low, the melting property and Young's modulus are likely to decrease. On the other hand, if the content of MgO is too high, the devitrification resistance and the strain point are likely to decrease.

[0030] CaO is a component that reduces high-temperature viscosity and significantly improves melting property without lowering the strain point. In addition, since the raw material introduced is relatively inexpensive among alkaline earth metal oxides, it is a component that reduces raw material costs. The CaO content is preferably 3 to 10%, 4 to 10%, and particularly 5 to 9%. If the CaO content is too low, it is difficult to enjoy the above effects. On the other hand, if the CaO content is too high, the glass is easily devitrified and the thermal expansion coefficient is easily increased.

[0031] SrO and BaO are components that increase the devitrification resistance, but also promote melt separation. Furthermore, they are components that reduce high-temperature viscosity and increase meltability without lowering the strain point, and also suppress the rise in liquidus temperature. The content of SrO is preferably 0 to 8%, 0.1 to 7%, and particularly 0.5 to 6%. The content of BaO is preferably 0 to 20%, 0.1 to 18%, 1 to 17%, 3 to 16%, and particularly 5 to 15%. If the content of SrO is too high, strontium silicate-based devitrification crystals are likely to precipitate, and the devitrification resistance is likely to decrease. If the content of BaO is too high, the density becomes too high and the meltability is likely to decrease. In addition, devitrification crystals containing BaO are likely to precipitate, and the liquidus temperature is likely to increase.

[0032] The alkaline earth oxides are components that reduce the high-temperature viscosity. The total amount of alkaline earth oxides (MgO+CaO+SrO+BaO) is preferably 1 to 40%, 5 to 30%, and particularly preferably 10 to 25%. If the content of MgO+CaO+SrO+BaO is too high, the glass is prone to devitrification. On the other hand, if the content of MgO+CaO+SrO+BaO is too low, the energy consumption for melting the glass batch increases, and the manufacturing cost of the glass becomes too high.

[0033] SnO2 is a component that acts as a clarifier, and its content is preferably 0 to 1%, 0.1 to 0.5%, and particularly preferably 0.2 to 0.4%. If the SnO2 content is too high, devitrified crystals are likely to precipitate, and the liquidus temperature is likely to rise.

[0034] ZrO2 is a component that easily causes devitrification, so the content of ZrO2 is preferably less than 0.5%, more preferably less than 0.2%, and it is particularly preferable that the glass does not contain ZrO2 except for unavoidable impurities.

[0035] SO3 is a component that causes foam defects due to reboiling of SO2 gas. If the content of SO3 is too high, foam defects due to reboiling of SO2 gas are likely to occur. The content of SO3 can be reduced by using a raw material with a low sulfur component, but this causes an increase in production costs. Therefore, the content of SO3 is preferably 0.1 to 100 ppm by mass, 0.5 to 50 ppm by mass, and particularly 1 to 10 ppm by mass.

[0036] In addition to the above components, other components may be added, such as ZnO, P2O5, F, Cl, and Mo. From the viewpoint of accurately enjoying the effects of the present invention, the content of other components other than the above components is preferably 10% or less in total, and particularly preferably 5% or less.

[0037] In the alkaline earth aluminosilicate glass according to the present invention, the strain point is preferably 650° C. or higher, 700° C. or higher, and particularly preferably 730 to 850° C. If the strain point is too low, the glass plate is likely to undergo thermal shrinkage during heat treatment in the display manufacturing process. On the other hand, if the strain point is too high, the manufacturing cost of the glass plate is likely to rise. The "strain point" refers to a value measured based on the method of ASTM C336.

[0038] In the alkaline earth aluminosilicate glass according to the present invention, 2.5 The temperature at dPa·s is preferably 1530 to 1680°C, more preferably 1550 to 1650°C, and particularly preferably 1580 to 1630°C. 2.5 If the temperature at 10 dPa·s is too low, it becomes difficult to control the deformation of the glass sheet during forming. 2.5 If the temperature at dPa·s is too high, the melting property decreases, and the manufacturing cost of the glass plate tends to rise. 2.5 The "temperature at dPa·s" can be measured by the well-known platinum sphere pulling method.

[0039] Next, after the preparation step, the obtained glass batch is charged into a melting furnace. The glass batch is usually charged into the melting furnace continuously by a raw material feeder such as a screw charger, but may be charged intermittently.

[0040] The glass batch introduced into the melting furnace is heated by a combustion atmosphere such as a burner or by electrodes and the like installed inside the melting furnace, and becomes a molten liquid.

[0041] The resulting melt is then subjected to a clarifying step, a stirring step, and a supplying step, and is then gradually cooled in order to be fed into a molding device.

[0042] The melt is then fed to a forming device and formed into a plate having a predetermined thickness and surface quality, and then cut to a predetermined size to become a glass product (glass plate). As a forming method, an overflow downdraw method, a float method, or the like can be adopted. In particular, the overflow downdraw method is preferred because it can produce an unpolished glass plate having a smooth surface.

[0043] The glass plate thus produced is suitably used as a substrate for, for example, a liquid crystal display, an organic EL display, or the like. EXAMPLES

[0044] The present invention will be described below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.

[0045] Table 1 shows samples No. 1 and No. 2.

[0046] [Table 1]

[0047] Each sample was prepared as follows. The raw materials were mixed to obtain the glass composition shown in the table, and a glass batch equivalent to 100 g of glass was prepared. The raw materials shown in the table were used as the raw materials for introducing the alkali metal oxide. "(Alkali metal derived from alkali feldspar raw material) / (Alkali metal in glass)" is the ratio of the mass% of the alkali metal oxide derived from the alkali feldspar raw material to the mass% of the alkali metal oxide in the glass. The raw materials other than the raw materials for introducing the alkaline earth metal oxide were exactly the same. The obtained glass batch was placed in a platinum alloy crucible having an approximately truncated cone shape, held at 1200°C for 1 hour, heated to 1600°C, melted for 2 hours, and then quenched. The glass was then peeled off from the crucible to obtain a glass sample having an approximately truncated cone shape with a diameter of 55 mm on the top surface, a diameter of 25 mm on the bottom surface, and a height of 25 mm, and the composition of the cross section 5 mm and 21 mm from the top surface was analyzed by XRF. "Silica top / bottom difference," "Alkaline earth oxide top / bottom difference," and "SO3 top / bottom difference" are values ​​obtained by subtracting the analysis value at 5 mm from the top from the analysis value at 21 mm from the top. The bubble density was calculated by immersing the glass between 5 mm and 21 mm from the top in a refractive index matching liquid and counting the number of bubbles.

[0048] As can be seen from the table, when alkali metal oxides were introduced from alkali feldspar raw materials, the absolute values ​​of the silica up-down difference, alkaline earth oxide up-down difference, and SO3 up-down difference were all smaller, and the bubble number density was smaller, than when alkali carbonates were used.

Claims

1. The method for producing alkaline earth aluminosilicate glass includes blending raw materials to prepare a glass batch, and then melting, fining, and forming the obtained glass batch to produce alkaline earth aluminosilicate glass, the method comprising the steps of: (a) preparing an alkaline earth aluminosilicate glass having an alkali metal oxide content of 0.01 to 1 mass %; and (b) using an alkali feldspar raw material as a raw material for introducing the alkali metal oxide.

2. A method for producing alkaline earth aluminosilicate glass as described in claim 1, wherein the BaO content in the alkaline earth aluminosilicate glass is 3 to 16 mass %.

3. The sulfur content in the alkaline earth aluminosilicate glass is SO 3 The method for producing alkaline earth aluminosilicate glass according to claim 2, wherein the content of said alkali metal ions in said glass is 0.1 to 100 ppm by mass.

4. B in alkaline earth aluminosilicate glass 2 O 3 The method for producing alkaline earth aluminosilicate glass according to claim 2 or 3, wherein the content of is 15 mass % or less.

5. 5. The method for producing alkaline earth aluminosilicate glass according to claim 2, wherein a total amount of alkaline earth metal oxides (MgO+CaO+SrO+BaO) in the alkaline earth aluminosilicate glass is 5 to 40 mass %.

Citation Information

Patent Citations

  • Glass and method for producing the same

    JP2006265001A

  • Method for producing silicate glass

    JP2012036075A

  • Method for producing glass substrate for liquid crystal display device

    JP2012148959A

  • Manufacturing method of glass plate

    JP2015187081A

  • Mixed material for silicate glass and method for manufacturing tube glass using same

    WO2017110927A1